Whitefly-Parasitoid-Insecticide Interactions: A Case Study Of Bemisia Tabaci Genn, 1889 (Hemiptera: Aleyrodidae), Encarsia Hitam Hayat, 2011 (Hymenoptera: Aphelinidae) And Selected Insecticides On Brinjal Plant Hosts (Solanum Melongena L.) (Family: Solanaceae) In The Field - Askarali, Nur Farhamizah (2013)
A field study was conducted to evaluate the effects of three insecticides (abamectin, malathion and diafenthiuron) on the interactions between Bemisia tabaci (Homoptera: Aleyrodidae) the brinjal pest, and the parasitoid Encarsia hitam (Hymenoptera: Aphelinidae), as well as on plant performances and fruit production. All insecticides were applied weekly at recommended doses over two brinjal cropping periods. Overall results showed high total numbers of whitefly on untreated plants in the first (14.08 ± 1.44 per leaf) and second (17.50 ± 4.65 per leaf) cropping periods compared to plants that were treated with abamectin (13.88 ± 3.32), malathion (9.80 ± 2.19 per leaf) and diafenthiuron (10.40 ± 2.41 per leaf) in the first crop and in second crop with 15.65 ± 5.42, 8.35 ± 2.79 and 9.48 ± 2.3 per leaf respectively. Malathion and diafenthiuron were the most effective insecticides that reduced whitefly populations below economic threshold level (ETL). Percentages of parasitism was high on whitefly nymphs in untreated control plants in the first and second cropping periods (3.17% - 12.82%) and (0.52% - 10.00%) respectively compared with insecticide-treated plants (0.62% - 12.50%) and (1.01% - 8.00%) respectively. All insecticides affected the parasitization of whitefly although no significance difference was observed among treatments.